The Relationship Between Knowledge About Complementary Feeding And Family Income With The Incidence Of Stunting - Poppy Siska Putri; Melisa Oktrinanda; Sekolah Tinggi Ilmu Kesehatan Sapta Bakt Syafitasari (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2025)
Background : Stunting has been a global health concern. The long-term consequences of stunting include high mortality and morbidity rates, suboptimal cognitive development, especially during school age, reduced work productivity, and future metabolic issues. Family income is a multidimensional factor. Additionally, the gap in knowledge regarding feeding remains a major issue. Objectives: The aim of this research is to determine the relationship between knowledge about complementary feeding and family income with the incidence of stunting. Method : This type of research uses a quantitative analytical observational method with a cross sectional design.  45 mother who met the selection criteria to participate in this study   were   obtained   by   simple   random   sampling technique. Result: The results of the univariate analysis showed that some respondents had less knowledge about complementary feeding (46.7%), some respondents had low income (55.6%) and  the majority of stunting respondents 26 (57.8%). The results of bivariate analysis using the Chi-Square statistical test found a significant relationship between maternal knowledge (p=0.002) and family income (p=0.001) with the incidence of stunting. Conclusion: Objectives: The aim of this research is to determine the relationship between knowledge about complementary feeding and family income with the incidence of stunting.